Exploring the relationship between vitamin B12, methylmalonic acid levels and all-cause mortality in heart failure populations: insights from the NHANES database - Yu, Wei; Wang, Yao; Zhou, Yulu; Wu, Danyu (Frontiers in Nutrition, 2025)
BackgroundA functional deficiency in vitamin B12 is a prevalent condition among heart failure (HF) patients. Despite being a specific and sensitive marker for this deficiency, the study of methylmalonic acid (MMA) in the context of HF has been infrequent.MethodsSeven hundred and forty-seven individuals with HF were incorporated in this cross-sectional study who participated in the National Health and Nutrition Examination Survey (NHANES) from two periods, 1999 to 2004, and 2011 to 2014. Hazard ratios (HRs) and 95% confidence intervals (CIs) of the risk of all-cause mortality were estimated using weighted multivariable Cox proportional hazard models. The non-linear association between MMA levels and all-cause mortality was investigated using restricted cubic spline (RCS) analyses.ResultsAmong 747 HF participants, 481 (57.3%) deaths were recorded during a follow-up period of 7.9 years. Elevated serum MMA levels were significantly associated with an increased risk of all-cause mortality (Tertile 3 compared with Tertile 1: adjusted HR: 1.52; 95% CI: 1.09, 2.13; p = 0.01), demonstrating a dose–response pattern (26% increased mortality risk per unit increase in lnMMA). B12 intake from diet was not significantly associated with mortality risk (p = 0.81). Although a minor statistically significant association was observed in serum B12 levels and mortality (p = 0.045), it disappeared after multivariate regression analysis. Moreover, the correlation between MMA and mortality risk was more prominent in HF populations with poorer health status, such as advanced age, current smokers, hypertension, diabetes, overweight, or low estimated glomerular filtration rate (eGFR).ConclusionOur study indicated that a higher MMA level is associated with an increased all-cause mortality risk in HF populations, particularly in those aged 65 and above, current smokers, those with hypertension, diabetes, overweight, insufficient physical activity, or lower eGFR (<60 mL/min/1.73 m2).